Psychological distress in Afghan journalists: a descriptive study. Issue 3 (12th June 2020) - Osmann, Jonas; Khalvatgar, Abdul Mujeeb; Feinstein, Anthony
Abstract : Purpose: Afghanistan is one of the world's most dangerous places for journalists. There are, however, no data on the mental health of Afghan journalists covering conflict in their country. The study aims to determine the degree to which Afghan journalists are exposed to traumatic events, their perceptions of organizational support, their rates of symptoms of posttraumatic stress disorder (PTSD) and depression, their utilization of mental health services and the effectiveness of the treatment received. Design/methodology/approach: The entire study was undertaken in Dari (Farsi). Five major Afghan news organizations representing 104 journalists took part of whom 71 (68%) completed a simple eleven-point analog scale rating perceptions of organizational support. Symptoms of PTSD and depression were recorded with the Impact of Event Scale – Revised (IES-R) and the Centre for Epidemiologic Studies Depression Scale (CES-D), respectively. Behavioral comparisons were undertaken between those journalists who had and had not received mental health therapy. Findings: The majority of journalists exceeded cutoff scores for PTSD and major depression and reported high rates for exposure to traumatic events. There were no significant differences in IES-R and CES-D scores between journalists who had and had not received mental health therapy. Most journalists did not view their employers as supportive. Originality/value: To the best of authors' knowledge, this is the first study to collect empirical data on the mental health of Afghan journalists. The results highlight the extreme stressors confronted by them, their correspondingly high levels of psychopathology and the relative ineffectiveness of mental health therapy given to a minority of those in distress. The implications of these findings are discussed.